The Strategic Performance of The Central Bank of India: A Mediat‎ing Role of Dynamic Capabilities and Moderating Role of Ambidexterity - Tripathi, Darpan; Ahmad, Shuhymee; M Sarkawi, Mohd Nizam (International Journal of Basic and Applied Sciences, 2025)
The purpose of this study was to understand the mediating role of dynamic capabilities and the moderating role of ambidexterity in the relationship between innovation capabilities, entrepreneurial capabilities, and strategic performance. The study was conducted in the context of the Central Bank of India, and data were collected based on a survey-based questionnaire. The branches of the Central Bank of India located in ‎Delhi, Mumbai, Chennai, Kolkata, Bangalore, and Lucknow were targeted, and a sample of 222 respondents was collected. Using Partial ‎Least Squares – Structural Equation Model, the study found that both innovation capabilities and entrepreneurial capabilities have a significant impact on dynamic capabilities and strategic performance. Furthermore, the study found that dynamic capabilities have a significant impact on strategic performance. The study found that dynamic capabilities significantly mediate the impact of innovation capabilities and ‎entrepreneurial capabilities on strategic performance. In addition, the study found that ambidexterity positively moderates the impact of ‎innovation capabilities on dynamic capabilities, while it has no moderating role for the impact of innovation entrepreneurial capabilities on ‎strategic performance. However, the study found that ambidexterity does not moderate the impact of dynamic capabilities on strategic performance‎.